ANALISIS KINERJA KEUANGAN CV. SAC BERSAUDARA SAMARINDA - Ivana Nina Esterlin Barus 3, Arief Solaiman 1, Mardiana 2 (EKONOMIA, 2020)
This research was conducted to determine and analyze the financial performance of CV. SAC Bersaudara from the aspect of liquidity ratios, aspects of solvency ratios, aspects of activities, and from the aspect of profitability ratios from 2015-2017.The analysis tools used in this study include current ratio, debt to asset ratio, total asset turnover, and return on assets.The results of the Current Ratio CV. SAC Bersaudara during 2015-2017 experienced fluctuations, where the Current Ratio in 2016 increased from 2015, but decreased in 2017. Debt to Asset Ratio CV. SAC Bersaudara during 2015-2017 experienced fluctuations, where the Debt to Asset Ratio in 2016 increased from 2015, but decreased in 2017. Total Assets Turn Over CV. SAC Bersaudara during 2015-2017 experienced fluctuations, where the Total Assets Turn Over in 2016 decreased from 2015, but experienced an increase in 2017. Return On Assets CV. SAC Bersaudara during 2015-2017 experienced fluctuations, where Return On Assets in 2016 decreased from 2015, but experienced an increase in 2017.Current Ratio CV. SAC Bersaudara during 2015-2017 were below industry standards. Debt to Asset Ratio CV. SAC Bersaudara during 2015-2017 were below industry standards. Total Assets Turn Over CV. SAC Bersaudara during 2015-2017 were below industry standards. Return On Asset CV. SAC Bersaudara during 2015-2017 were below industry standards.